Efeitos dos moduladores seletivos de receptores de estrogenio na reatividade vascular de anéis de aorta e em biomarcadores inflamatórios cardíacos de fêmeas ovariectomizadas - Lamas, Aline Zandonadi (2015)
The selective estrogen receptors modulators (SERMs), raloxifene and tamoxifen, can be are used in clinical practice for osteoporosis and breast cancer, respectively. However, the effects of SERMs on the system of atrial natriuretic peptide (ANP) and proteins involved in the inflammatory process and its effects on vascular reactivity of aortic rings, have not been determined in the literature. In this study we investigated the influence of raloxifene and tamoxifen in the system of natriuretic peptides in cardiac remodeling biomarkers - tumor necrosis factor-alpha (TNF-α) and p65 subunit of nuclear factor kappa B (NFkB). Studies of the influence of SERMs on endothelial modulation of vascular tone in aortic rings were also conducted. The female rats were divided into five groups: SHAM, OVX (ovariectomized), OVX treated with 17β-estradiol (EST) OVX treated with raloxifene (RAL) and OVX treated with tamoxifen (TAM). The treatments started 21 days after ovariectomy and lasted 14 days Ovariectomy promoted an increase in responsiveness to phenylephrine and an attenuation of the acetylcholine-induced relaxation in aortic rings. In the presence of aminoguanidine (50 mM) did not change in Emax. In the presence of L-NAME (100 mM) there was an increase in Emax in all groups, indicating the importance of the nitric oxide in all groups. In the presence of apocynin (0.3 mM) there was a decrease in Rmax in all groups, it was significant in the OVX group compared to the control situation. Plasma levels,and mRNA expression of ANP in left atrial tissue were reduced in the OVX group. Treatment with 17βestradiol and SERMs normalized as plasma ANP, ANP mRNA in left atrium. These parameters were not altered in the right atrium. Protein expression of TNF-α and NF-kB p65 subunit presented increased in OVX but were normalized by the treatments, except for the raloxifene group in relation to TNF-α expression The treatment with SERMs promoted numerous benefits, demonstrating antiinflammatory effects similar to normalize the plasma levels of ANP and important biomarkers involved in cardiac remodeling. As well as normalized the vasoconstrictor and vasodilator response of aortic rings. Therefore, these treatments may be important contributors in preventing cardiovascular diseases that affect primarily women in the post menopausal phase.